Strategi Pembelajaran Guru Pendidikan Agama Buddha Sekolah Dasar pada Siswa yang Memiliki Kesulitan Belajar - Lestari, Vidi; Suranto; Waluyo (STAB Kertarajasa, 2025)
Learning difficulties experienced by students become obstacles to the optimal implementation of the learning process. Appropriate and effective teacher strategies are therefore needed to address the learning challenges faced by students. Accordingly, this study aims to analyze the strategies applied by Buddhist Religious Education teachers in assisting students who experience learning difficulties at the elementary school level at SD Negeri Getas. This research employs a descriptive qualitative approach with a case study design to gain an in-depth understanding of the background of the problems and challenges faced by students in the learning process. Data were collected through observation, interviews, and documentation. The research subjects consisted of teachers and students who face various learning difficulties, including supporting and inhibiting factors in the learning process. The results indicate that the teachers implemented various learning strategies to overcome students’ learning barriers, which successfully reduced passive attitudes and increased student participation in the classroom. The problem-based learning (PBL) strategy is relevant in encouraging students to think critically and actively ask questions. The discovery approach helps overcome reading and writing difficulties, thereby increasing students’ motivation and self-confidence.